2019
DOI: 10.1111/asap.12187
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Dehumanization in Everyday Policing: The Psychological, Affective, and Material Consequences of Discretionary Arrests

Abstract: Amid aggressive surveillance and policing practices, Black Lives Matter has appeared-a social movement whose very name highlights collective resistance to pervasive dehumanization. Psychological studies find the persistent dehumanization of people of color and endorsement of legitimated violence against those dehumanized. As part of broken windows policing, people of color also disproportionately experience discretionary arrests, or charges for low-level, nonviolent offenses legally recognized as noncriminal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 86 publications
(105 reference statements)
0
4
0
Order By: Relevance
“…Concerns regarding criminal justice practices were rarely mentioned ( n = 1; .04%). This absence is particularly noteworthy given the well-documented racial and economic disparities in treatment by law enforcement and high levels of distrust in the police in communities of color, factors that may discourage marginalized survivors from seeking police intervention (Bustamante, Jashnani, & Stoudt, 2019; Cramer, 2005; Richie, 2012). Battered women who do call the police may risk dual arrest, which could lead to eviction, loss of income, foster care placement, or loss of public benefits, consequences that are disproportionately experienced by Black and Latinx women (Rajah et al, 2006; Richie, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Concerns regarding criminal justice practices were rarely mentioned ( n = 1; .04%). This absence is particularly noteworthy given the well-documented racial and economic disparities in treatment by law enforcement and high levels of distrust in the police in communities of color, factors that may discourage marginalized survivors from seeking police intervention (Bustamante, Jashnani, & Stoudt, 2019; Cramer, 2005; Richie, 2012). Battered women who do call the police may risk dual arrest, which could lead to eviction, loss of income, foster care placement, or loss of public benefits, consequences that are disproportionately experienced by Black and Latinx women (Rajah et al, 2006; Richie, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In cases of perceived existential threats, such fury is often intensified by imagery of moral depravity, in which the enemy is cast as inherently immoral, degenerate, or demonic (Bruneau et al, 2018; Bustamante et al, 2018, 2019; Kteily & Landry, 2022; Landry et al, 2021; Lang, 2020). The politics of White rage traffics in such imagery, driven by the fear that the nation’s pure people—White Christians—are experiencing existential threats (Ott & Dickinson, 2019, Chapter 2).…”
Section: What Is Righteous Rage?mentioning
confidence: 99%
“…Unlawful or discretionary arrests—charges for low-level and nonviolent offenses that are legally recognized as noncriminal—and unwarranted detainments, the third category on the Continuum, describe instances in which police unjustly or without cause arrest or temporarily detain people; experiences that are disproportionately higher for Black people than White people in the United States (Bustamante et al, 2019). Analyses of city and county police arrest data voluntarily reported to the FBI showed that in 800 jurisdictions, Black people were five times more likely to be arrested than White people, after controlling for the demographics of the cities and counties served; in 250 jurisdictions, Black people were 10 times more likely to be arrested than White people (Thomas et al, 2020).…”
Section: The Anti-black Police Brutality Continuummentioning
confidence: 99%